IDENTIFIKASI JEJARING PENGELOLAAN KONSERVASI PENYU HIJAU (Chelonia mydas) MELALUI PENENTUAN KOMPOSISI GENETIK DAN METAL TAG DI LAUT SULU SULAWESI - Ni Kadek Dita Cahyani; I.B. Windia Adnyana; I W. Arthana (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science))
The research used 51 tissue samples taken from 51 individual Green Turtles in Pulau Panjang, EastKalimantan. The isolation of mtDNA was achieved by adding Proteinase K into the samples prior to the utilization ofthe PCR (Polimerase Chain Reaction) technique. The MEGA 3.1 computer program was employed to read the DNAsequences obtained through the PCR technique.Seven different haplotypes were identified from the analyzed samples. The haplotypes are: A3 (N=7; 13.73%),A4 (N=1; 1.96%), A6 (N=2; 3.92%), C3 (N=5; 9.80%), C5 (N=6; 11.76%), C14 (N=5; 9.80%) dan D2 (N=25;49.02%). Tag findings clearly demonstrated that the Green Turtles, which feed on the seagrass beds of Pulau Panjang,originated in different nesting sites, including Sabah and Trengganu in Malaysia, Sangalaki and Derawan inIndonesia, and Phillipine. The MSA (Mixed Stock Analysis) showed that the Green Turtles population in PulauPanjang was composed of several management units (nesting sites), which were Berau (47%), Sulu Sea (34%) andMicronesia (6%).